Recent Advances in Multi-Paradigm Modeling - Amaral, Vasco; Hardebolle, Cécile; Vangheluwe, Hans; Lengyel, László; Bunus, Peter (Electronic Communications of the EASST, 2012)
<!–StartFragment–>Following the trend of other editions, it was held this year (2011) in Wellington, New Zealand, the 5th International Workshop on Multi-Paradigm Modelling: Concepts and Tools (MPM). Once again has been a satellite event of the International Conference on Model-Driven Engineering Languages and Systems (MoDELS). It aims at further the state-of-the-art as well as to define future directions of this emerging research area by bringing together world experts in the field for an intense one-day workshop. This paper summarizes the results of this year’s event.<!–EndFragment–>